Forecasting Production Growth of Micro and Small Textile Industries Using SARIMA - Cahyaningrum, Nafisah Hanan; Yotenka, Rahmadi; Suparna (Enthusiastic : International Journal of Applied Statistics and Data Science, 2026)
Micro and small industry (MSME) is an industrial sector that includes small-scale businesses, both those with limited assets and turnover. MSME is an industrial business that is mostly labor-intensive and plays a role in creating jobs and driving the local economy. One of the largest industries in MSME is the textile industry. Production in the textile industry tends to fluctuate due to market demand, availability of raw materials, and economic conditions. Understanding the dynamics of market demand is very important for the government and business actors in making decisions. This study aimed to predict the growth of MSME production in the textile industry using the seasonal autoregressive integrated moving average (SARIMA) method. Several SARIMA models were used to predict the growth of MSME production in the textile industry. However, only the model with the smallest AIC value was selected to predict the growth of MSME production in the textile industry. The prediction results showed that fluctuations occurred in the growth of the textile industry in each period.